Effects of visualisation and advance organisers in reading multimedia-based texts - Roohani, Ali; Jafarpour, Aliakbar; Zarei, Solmaz (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
Recent advancements in multimedia systems to integrate text, audio, graphics, and video have created a new interest in using instructional strategies in a multimedia-based learning environment. In this light, this study explores the effect of two types of visualisations (static and animated) and advance organisers (descriptive and question) on EFL learners’ reading comprehension in a multimedia context. To this end, a software program with four computer-based modules was designed to show texts with four instructional formats - texts with static visual embedded descriptive advance organisers, texts with static visual embedded question advance organisers, texts with animation embedded descriptive advance organisers, and texts with animation embedded question advance organisers. Eighty intermediate Iranian EFL learners, who were selected from three language institutes through a placement test, were randomly assigned to one of four computer-based instructional formats: the first group read texts with static visual embedded descriptive advance organisers, the second group had texts with static visual embedded question advance organisers, the third group read texts with animation embedded descriptive advance organisers, and the fourth group had texts with animation embedded question advance organisers. Once the EFL learners interacted with their respective instructional materials, they then took a reading comprehension test. The results revealed that the question type of advance organiser was more effective than the descriptive one; the animation type of visualisation was more effective than the static one and embedding animations with question advance organisers improved reading comprehension significantly. The findings imply the integration of advance organisers with computer-generated visuals in multimedia reading programs cue attention of L2 students to salient features conveyed in the reading texts and visuals.